THE IMPLEMENTATION OF WRITING ASSESSMENT BASED ON KTSP (SCHOOL-BASED CURRICULUM) AT SMAN 2 SOLOK - Karyawetti, Yunita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
The aim of the research is to describe how the English teachers of SMAN 2 Solok implement School-Based Curriculum in writing assessment which consists of Genre - Based Assessment (portfolio), Curriculum - Oriented Assessment (Competence - Based Assessment and Process - Oriented Assessment), and criteria of writing assessment (social function, generic structure, and language features). Beside that this research is also aimed to find out the problems they face in assessing the students’ writing. The research is descriptive which applied qualitative method. The data were collected by interviewing, observing the process, and examining the documentation of the informants (six informants which two of them were key informants). The researcher found that (1) three English teachers have implemented portfolio assessment, (2) all English teachers have implemented competence-based assessment, (3) three English teachers have implemented process-oriented assessment, and (4) all English teachers have considered criteria in writing assessment although two of them still did not consider language features of the students’ writing.